Bacterial Surface-Displayed GII.4 Human Norovirus Capsid Proteins Bound to HBGA-Like Molecules in Romaine Lettuce - Wang, Ming; Rong, Shaofeng; Tian, Peng; Zhou, Yue; Guan, Shimin; Li, Qianqian; Wang, Dapeng (Frontiers in Microbiology, 2017)
Human Noroviruses (HuNoVs) are the main cause of nonbacterial gastroenteritis. Contaminated produce is a main vehicle for dissemination of HuNoVs. In this study, we used an ice nucleation protein mediated surface display system to present the protruding domain of GII.4 HuNoV capsid protein on bacterial surface and used it as a new strategy to explore interaction between HuNoV protein and receptor candidates from romaine lettuce. The surface-displayed HuNoV proteins were confirmed on the surface of the transformed bacteria by an immunofluorescence assay. The distribution patterns of the surface-displayed HuNoV proteins in romaine lettuce were identified through a confocal immunofluorescence assay. The surface-displayed HuNoV proteins could be found in the stomata, and the surfaces of vein and leaf of romaine lettuce. The surface-displayed HuNoV proteins could be captured by an ELISA assay utilizing extract from leaf (LE) or vein (VE). The binding of the surface-displayed HuNoV proteins to LE or VE could be competitively blocked by histo-blood group antigens from human saliva. In addition, the binding of the surface-displayed HuNoV proteins to LE or VE could also be attenuated by heat denaturation of lettuce proteins, and abolished by oxidation of lettuce carbohydrates. The results indicated that histo-blood group antigen-like molecules in LE or VE were involved in the binding of the surface-displayed HuNoV proteins to romaine lettuce. All data demonstrated that the surface-displayed HuNoV proteins could be utilized in a new and simple system for investigation of the interaction between the HuNoVs and their candidate ligands.